Meneropong Prospek Pemberlakuan PAS-FINAL (Pengungkapan Aset Sukarela dengan Tarif Final) Pasca Tax Amnesty untuk Meningkatkan Penerimaan Negara - Safrina, Noor (Simposium Nasional Keuangan Negara, 2018)
Since the issuance of PMK-165 / PMK.03 / 2017 concerning tax amnesty, is one of the motivations to encourage taxpayer compliance, namely PAS-Final or Voluntary Asset Disclosure with Final rates. The purpose of this study is to find out and evaluate the meaning of the PAS-FINAL program in increasing tax revenues both in the long and short term. This research method is a qualitative approach with descriptive analysis method, which reveals events or facts, which occur when the research takes place by presenting what actually happened. This study interprets and describes the data concerned with the current situation, namely events or activities related to the implementation of the PAS-FINAL program as an effort to increase state revenues, especially taxes. The output of this research is in the form of policy references for the Directorate General of Taxes that PAS-FINAL should not be intended for Taxpayers who have participated in the Tax Amnesty program. Where if there is a Tax Amnesty participant who forgets when reporting assets, then is found during the investigation and investigation then sanctions and penalties will be imposed according to the rules. Previously the government had promised that Tax Amnesty participants had legal certainty. The law guarantees that if you participate in Tax Amnesty honestly and get a certificate, it is guaranteed that you will not be examined so that tax officials cannot take any action. Keywords: PAS-FINAL Program, State Revenue, Taxpayers